A vector based approach for high frequency prospective correction of rigid body motion in Magnetic Resonance Imaging (MRI) - Van Niekerk, Adam Marthinus Johannes (Department of Human Biology, 2019)
Magnetic Resonance Imaging (MRI) is remarkable in that it is possible to obtain image resolutions much smaller than the wavelength of the radiated signal. This is achieved through the use of specialised gradient coils that linearly manipulate the magnitude of the magnetic field within the imaging volume. The instantaneous signal received from the subject represents a periodically varying map based on the duration and magnitude (moment) of the previously applied gradient fields. Representing an object as the sum of periodic maps is difficult and as a result many unique gradient moments are required to form an image. When the subject moves the periodic maps are no longer coherent and the constructive/destructive interference becomes invalid. The artefacts are dependent on how and when motion occurred, and manifest as ghosting, ringing and blurring of the image. This thesis describes a novel approach to measuring and correcting for motion as the data are acquired. A small device was constructed that combines observations from a magnetometer (static magnetic field [z]) and an accelerometer (earth’s gravitational field [y]) with an angular rate sensor to determine its orientation with respect to the imaging coordinate frame (VectOrient). It was precise enough to track the subject’s heart beat and breathing and accurate to within one degree. A gradient field probe was then designed for position encoding. The probe measured the rate of change of the gradient magnetic fields using three mutually orthogonal pickup coils. Assuming linear gradients and using Maxwell’s equations, with negligible rates of change of curl and divergence, it was possible to accurately model the three dimensional vector fields that the gradients produce, eliminating the need for a laborious manual calibration. Sub-microsecond synchronisation was achieved by detecting radio frequency pulses in the imaging sequence with a small resonant circuit. This combined with a 2.4 GHz radio link enabled the probe to be wireless. Finally, the pickup coil observations were combined with the vector based orientation estimates and the gradient field model to achieve efficient multidimensional position, orientation and inter-gradient-delay encoding with a 880 µs pulse sequence insert. The Wireless Radio frequency triggered Acquisition Device (WRAD) tracks involuntary and deliberate subject motion, improving image quality without scanner specific calibration.